Is Bigger Better? Living Donor Kidney Volume as Measured by the Donor CT Angiogram in Predicting Donor and Recipient eGFR after Living Donor Kidney Transplantation - Chaudhry Adeel Ebad; David Brennan; Julio Chevarria; Mohammad Bin Hussein; Donal Sexton; Douglas Mulholland; Ciaran Doyle; Patrick O’Kelly; Yvonne Williams; Ruth Dunne; Conall O’Seaghdha; Dilly Little; et al. (Journal of Transplantation)
Background. The role of kidney volume measurement in predicting the donor and recipient kidney function is not clear. Methods. We measured kidney volume bilaterally in living kidney donors using CT angiography and assessed the association with the donor remaining kidney and recipient kidney (donated kidney) function at 1 year after kidney transplantation. Donor volume was categorized into tertiles based on lowest, middle, and highest volume. Results. There were 166 living donor and recipient pairs. The mean donor age was 44.8 years (SD ± 10.8), and donor mean BMI was 25.5 (SD ± 2.9). The recipients of living donor kidneys were 64% male and had a mean age of 43.5 years (SD ± 13.3). Six percent of patients experienced an episode of cellular rejection and were maintained on dialysis for a mean of 18 months (13–32) prior to transplant. Kidney volume was divided into tertiles based on lowest, middle, and highest volume. Kidney volume median (range) in tertiles 1, 2, and 3 was 124 (89–135 ml), 155 (136–164 ml), and 184 (165–240 ml) with donor eGFR ml/min (adjusted for body surface area expressed as ml/min/1.73 m2) at the time of donation in each tertile, 109 (93–129), 110 (92–132), and 101 ml/min (84–117). The median (IQR) eGFR in tertiles 1 to 3 in kidney recipients at 1 year after donation was 54 (44–67), 62 (50–75), and 63 ml/min (58–79), respectively. The median (IQR) eGFR in tertiles 1 to 3 in the remaining kidney of donors at 1 year after donation was 59 (53–66), 65 (57–72), and 65 ml/min (56–73), respectively. Conclusion. Bigger kidney volume was associated with better eGFR at 1 year after transplant in the recipient and marginally in the donor remaining kidney.